Honghua Xiaoyao tablet combined with estradiol improves ovarian function in D-galactose-induced aging mice by reducing apoptosis and affecting the release of reproductive hormones: an in vivo study - Chan Su; Chan Su; Ruihong Zhang; Xiujuan Zhang; Xiaoning Feng; Qiong Wu; Yiwei Gao; Jing Hao; Yu-lan Mu (Frontiers Media S.A., 2024)
Context: It is very necessary to delay ovarian aging and prevent age-related health problems. The active ingredient in Honghua Xiaoyao tablet (HHXYT) has the effects of anti-oxidation, anti-inflammation, immune regulation and so on.Objective: To explore the effect and mechanism of Honghua Xiaoyao tablet on aging model mice.Materials and methods: The aging model was established by intraperitoneal injection of D-galactose in model mice. The mice in the HHXYT-L,M,H group were given 0.3 g/kg, 0.6 g/kg and 1.2 g/kg Honghua Xiaoyao tablet suspension respectively, and the HHXYT-M + E2 group was given 0.6 g/kg HHXYT +0.13 mg/kg estradiol valerate for 30 days. In this study, ELISA, HE, Western blot, IH and TUNEL were used.Results: HHXYT + E2 can improve the gonadal index, estrous cycle of aging mice. In HHXYT-M + E2 group, the level of FSH and LH decreased, while E2 and AMH increased significantly. The number of growing follicles in HHXYT-M + E2 group increased, which was better than that of HHXYT alone. Western blot results showed that HHXYT-M + E2 group decreased the expression of Bax, cleaved-Parp, cleaved-Casp-3 and CytC molecules and increased the expression of Bcl-2 in ovarian tissue. FSHR expression decreased in model group and increased in HHXYT group. TUNEL staining showed that the number of apoptotic cells in HHXYT group was reduced, and the HHXYT-M + E2 group was the most significantly.Discussion and conclusion: HHXYT can improve the level of sex hormones and increase the number of growing follicles in aging mice. HHXYT-M + E2 group has the best effect, and its mechanism may be related to reducing ovarian granulosa cell apoptosis.